Gendered Perspectives in Pop Lyrics: A Linguistic Analysis of Bruno Mars’ “When I Was Your Man” and Miley Cyrus’ “Flowers” - Melany Renita Manullang; Yuli Charina Br Ginting Manik; Rosa Darliana Br Tarigan; Julia Carolina Br Ginting; Vivi Novalia Sitinjak (Jurnal Dieksis ID, 2026)
This study is urgent because a gendered linguistic analysis of “When I Was Your Man” and “Flowers” reveals how popular music constructs, reinforces, or challenges contemporary gender perspectives and relationship narratives. This study examines gendered perspectives in pop song lyrics through a qualitative linguistic analysis of Bruno Mars’ “When I Was Your Man” and Miley Cyrus’ “Flowers.” The main research objectives are to identify and compare the linguistic features used to construct gendered voices in both songs and to analyze how emotional expression and self-identity are represented through these gendered perspectives. Song lyrics function as cultural texts that reflect social constructions of gender, particularly in emotional expression and identity formation. Previous studies have largely focused on female representation or gender bias using semiotic, discourse, or computational approaches, leaving a gap in comparative linguistic analysis across genders. To address this gap, this research applies lexical, semantic, and syntactic analysis within the framework of gender and language studies. The data consist of the official lyrics of the two songs, collected through documentation techniques and analyzed qualitatively. The findings reveal clear contrasts between male and female perspectives. The male perspective is characterized by lexical choices expressing regret and emotional vulnerability, semantically framing love as loss, and syntactically relying on reflective and conditional structures. In contrast, the female perspective emphasizes empowerment and independence through assertive diction, self-directed meaning, and simple declarative sentence patterns. This study contributes to gender and language research by offering a comparative linguistic perspective on how male and female identities are constructed in contemporary pop music.